Issues of Women's Rights in the Jadid Movement - Nilufar D. Djuraeva (Universitas Muhammadiyah Sidoarjo, 2024)
This article delves into the Jadidist movement's influence on women's rights and gender equality within Uzbekistan, emphasizing the pivotal role of enlightened women in societal development. Through the lens of the Jadids' mantra of